Cluster Preface: Process Chemistry - Yasuda, Nobuyoshi (Synlett, 2013)
The goal of process chemistry is to identify cost-effective, robust and environmentally friendly manufacturing routes for drug candidates. This article outlines the importance of scientific innovation to overcome the many challenges along the journey towards a drug filing.
Keywords: manufacturing processes; cost efficiency; reproducibility; ease of operation; safety; green chemistry; reaction mechanisms